The consumption of the carp meat and plasma lipids in secondary prevention in the heart ischemic disease patients - Adámková, Vera; Kacer, Petr; Mraz, Jan; Suchanek, Pavel; Pickova, Jana; Králova Lesná, Ivana; Skibova, Jelena; Kozak, Pavel; Maratka, Vit (Neuro endocrinology letters, 2011)
OBJECTIVES: Omega-3 fatty acids (FA) have been shown to be protective against cardiovascular diseases (CVD). The effect of the consumption of carp meat on CVD risk factors has not yet been examined in detail. We ascertained the influence of a diet enriched with carp meat with an elevated content of omega-3FA (200 g twice weekly for 4 weeks) in a group of subjects after cardiac revascularization surgery for ischemic heart disease with a follow-up spa treatment. DESIGN: After cardiac revascularization surgery, the probands consumed either a standard spa diet (56 individuals, 41 males, 15 females, age 41-80 years) or a diet enriched with two portions of carp meat (87 individuals, 64 males, 23 females, age 50-82 years). The differences in body mass index (kg/m²), blood pressure, plasma lipids and C-reactive protein (CRP) of the groups were analyzed. RESULTS: In the group with a higher consumption of carp meat, significantly greater improvements in lipid parameters in comparison to the standard spa diet were detected (total cholesterol p<0.001, triglycerides p<0.001, LDL-C p<0.001, CRP p<0.001, HDL-C p<0.001). No differences between these groups in blood pressure and body mass index were found. CONCLUSION: We conclude that the diet enriched with carp meat significantly improved plasma lipid parameters in patients after major cardiac revascularization surgery.
Keywords: dospělí; Animals; Fatty Acids, Omega-3; revaskularizace myokardu; Female; Myocardial Ischemia; LDL-cholesterol; C-Reactive Protein; Adult; Cholesterol, LDL; ženské pohlaví; kapři; lipidy; Myocardial Revascularization; lidé; maso; ischemická choroba srdeční; Meat; Lipids; Aged, 80 and over; krevní tlak; dieta; Humans; omega-3 mastné kyseliny; sekundární prevence; Diet; Male; Secondary Prevention; Aged; Czech Republic; index tělesné hmotnosti; HDL-cholesterol; Carps; Česká republika; lidé středního věku; C-reaktivní protein; senioři nad 80 let; senioři; zvířata; mužské pohlaví; Blood Pressure; Body Mass Index; Middle Aged; Cholesterol, HDL